Structure Design and Deflection Analysis of the New Large Deflection Lamina Emergent Joints - Liu Qingling (Jixie chuandong)
Two kinds of large deflection plane folding hinges, named OSD-LEJ (outside-series-deployed lamina emergent joint) and IOSD-LEJ (inverted-outside-series-deployed lamina emergent joint), are designed with flexible segments arranged in series on the outside, taking into account the inverted design principle. The structures of the two LEJs are designed, and the bending equivalent stiffness formulas are derived. Through the theoretical calculation and the finite element simulation analysis of OSD-LEJ and IOSD-LEJ, the errors between them are about 4% and 4.2% respectively. The correctness of the bending equivalent stiffness formulas is verified. The performances of OSD-LEJ, IOSD-LEJ and large deformation OD-LEJ in the literature with the same feature size are compared and analyzed. The results show that the bending deflections of OSD-LEJ and IOSD-LEJ are 1.2 times and 1.31 times those of the OD-LEJ respectively and the tensile deflections of OSD-LEJ and IOSD-LEJ are 1.16 times and 1.18 times those of the OD-LEJ respectively. Therefore, the OSD-LEJ and IOSD-LEJ have better comprehensive performance. The validity and rationality of structure design of the joints are verified; the idea and reference for the structure design of large deformation hinge LEJ are provided.